The Impact of the Baamboozle Educational Game on Phase E Students' Learning Outcomes at SMA Negeri 1 Candung - Anissa Trifani Rahmi; Shindu Krisnanda (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2026)
This study focuses on low student engagement and suboptimal utilization of learning media, which impacts on exercise and exam scores that have not reached the minimum standard of 75. To improve learning outcomes, this study utilizes the Baamboozle educational game media, a web-based quiz designed to make learning more interactive, fun, and able to increase student participation. The purpose of this study is to analyze learning outcomes before and after the implementation of Baamboozle, as well as measure its effect on student achievement in phase E. This study uses a quantitative approach with a quasi-experimental design of the Pretest-Posttest Control Group model. The sample was selected purposively from phase E students of SMA Negeri 1 Candung, consisting of 29 students of class E3 as the experimental group and 29 students of class E2 as the control group. Data collection was carried out through pre-tests and post-tests. The hypothesis was tested with the criteria H0 is accepted if the significance value is >0.05, while H1 is accepted if <0.05. The results of the analysis show that the significance value of the two-tailed test in both classes is 0.000 (<0.05), so H0 is rejected and H1 is accepted. The t-test on the posttest also produced a significance value of 0.001 (<0.05), which means that Baamboozle has a significant influence on the learning outcomes of phase E students at SMA Negeri 1 Candung.